PERDA SYARIAH DALAM PERSPEKTIF POLITIK ISLAM DAN RELIGIUSITAS UMAT DI INDONESIA - Efrinaldi, Efrinaldi (Madania: Jurnal Kajian Keislaman, 2014)
Islamic Local Regulations in the Perspective of Islamic Politics and Religious Society in Indonesia. Afterreformation, the spectrum of political view in Indonesia has rapidly increased. One of the political progressessigned by local regulations that regulate some aspects of Islamic teaching is regarded as Islamic regulation.There are many regions and cities in Indonesia that applied the regulation, while other regions and cities havebeen managing the same draft through the government and legislative assembly. To improve religiosity forall, the coming Islamic-nuanced regulation is something needed significantly. In addition, implementation ofIslamic regulation in any places can encourage awareness to do the best things among communities. Islamiclegalization through Islamic regulation in public area, however, has indicated that Islam performs expressively.In some regions, for instance, there is a regulation that forces Muslim people to wear Islamic clothing and toread the Qur’an every day. The Motivation of undertaking this regulation is influenced by the theory of receptiea contrario. Looking at that theory, all Muslims should apply and do Islamic teachings because they are obligatedto do that totally. Besides, there is no force for non-Muslim people compulsively to apply such Islamic teachings